2019
DOI: 10.1136/tsaco-2019-000367
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Embolic Scoring System in military trauma: a sensitive predictor of venous thromboembolism

Abstract: IntroductionClinical decision support tools capable of predicting which patients are at highest risk for venous thromboembolism (VTE) can assist in guiding surveillance and prophylaxis decisions. The Trauma Embolic Scoring System (TESS) has been shown to model VTE risk in civilian trauma patients. No such support tools have yet been described in combat casualties, who have a high incidence of VTE. The purpose of this study was to evaluate the utility of TESS in predicting VTE in military trauma patients.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Factors identified by our clinical and injury models are similar to those seen in separate studies of risk factors for VTE after severe military and civilian trauma. [ 10 , 23 , 26 , 40 , 41 ] Similar predictive models have also implicated several risk factors we identified including injury severity, spinal injury, and other orthopaedic injuries, with a similar predictive power, although these did not evaluate TXA use and none exclusively considered patients with orthopaedic injuries. [ 42 44 ]…”
Section: Discussionmentioning
confidence: 88%
“…Factors identified by our clinical and injury models are similar to those seen in separate studies of risk factors for VTE after severe military and civilian trauma. [ 10 , 23 , 26 , 40 , 41 ] Similar predictive models have also implicated several risk factors we identified including injury severity, spinal injury, and other orthopaedic injuries, with a similar predictive power, although these did not evaluate TXA use and none exclusively considered patients with orthopaedic injuries. [ 42 44 ]…”
Section: Discussionmentioning
confidence: 88%
“…Studies suggest that an optimal high-risk cut-off value of TESS ≥7 demonstrates a high sensitivity in predicting VTE. 53 , 54 …”
Section: Diagnosis Of Traumatic Vtementioning
confidence: 99%
“…Patients with a TESS ≥7 is at a high risk of VTE and should receive prophylaxis earlier. 53 , 54 Studies have shown that an ISS ≥10 suggests that pharmacologic prophylaxis should be initiated as soon as possible, whereas patients with an ISS<10 are at a lower VTE risk and may not require pharmacologic prophylaxis. 46 , 53 Patients with minor trauma may not require pharmacologic prophylaxis.…”
Section: Treatment and Prevention Of Trauma Vtementioning
confidence: 99%
“…The retrospective MATTERs (military application of tranexamic acid in trauma emergency resuscitation) study demonstrated that the rate of all-cause mortality among patients who underwent emergency resuscitation in military combat was significantly lower among those who received TXA than those who did not (17.4% vs. 23.9%), but VTE incidence in the TXA group was about 10 times that in the untreated group [ 65 ]. A retrospective cohort study of 549 combat casualties admitted to US military hospitals from October 2010 to November 2012 also indicated that TXA was an independent risk factor for the development of VTE [ 66 ]. According to a retrospective analysis of 3773 military casualties, the use of TXA was not associated with mortality but did increase the risk of VTE [ 67 ].…”
Section: Pathophysiological Mechanismmentioning
confidence: 99%